2007
DOI: 10.1085/jgp.200709872
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 Mutations Alter Ion Permeation and Ca2+-dependent Fast Inactivation of CRAC Channels: Evidence for Coupling of Permeation and Gating

Abstract: Ca2+ entry through store-operated Ca2+ release-activated Ca2+ (CRAC) channels is an essential trigger for lymphocyte activation and proliferation. The recent identification of Orai1 as a key CRAC channel pore subunit paves the way for understanding the molecular basis of Ca2+ selectivity, ion permeation, and regulation of CRAC channels. Previous Orai1 mutagenesis studies have indicated that a set of conserved acidic amino acids in trans membrane domains I and III and in the I–II loop (E106, E190, D110, D112, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
219
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(245 citation statements)
references
References 44 publications
25
219
1
Order By: Relevance
“…2 E and F; n ϭ 10 cells). With an estimated permeability ratio P Cs /P Na ϭ 0.73 Ϯ 0.07 calculated by the Goldman-Hodgkin-Katz equation (29), the Orai3-Orai1 tandem is dramatically less selective for Na ϩ over Cs ϩ under divalent-free conditions in comparison to 0.18 Ϯ 0.02 for Orai1 and 0.11 Ϯ 0.02 for Orai3 in line with a previous calculation of 0.15 for Orai1 currents (24). Native CRAC channels (30) in Jurkat T-cells yielded P Cs /P Na ϭ 0.13.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…2 E and F; n ϭ 10 cells). With an estimated permeability ratio P Cs /P Na ϭ 0.73 Ϯ 0.07 calculated by the Goldman-Hodgkin-Katz equation (29), the Orai3-Orai1 tandem is dramatically less selective for Na ϩ over Cs ϩ under divalent-free conditions in comparison to 0.18 Ϯ 0.02 for Orai1 and 0.11 Ϯ 0.02 for Orai3 in line with a previous calculation of 0.15 for Orai1 currents (24). Native CRAC channels (30) in Jurkat T-cells yielded P Cs /P Na ϭ 0.13.…”
Section: Resultssupporting
confidence: 83%
“…The narrowest part of the Orai1 and Orai3 pore is approximately 3.8 Å (23,24), suggesting that steric hindrance most likely accounts for low Cs ϩ permeability in homomeric Orai channels. Therefore, increased Cs ϩ permeability and consequently reduced Ca 2ϩ selectivity is a fingerprint of the heteromeric assembly of Orai1 and Orai3 proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Srikanth et al suggest that the II-III loop of Orai1 may function as a blocking particle in CDI to inhibit conduction. Another study has shown that mutations that increase Orai1 pore size (E106D, E190Q) greatly reduce or eliminate CDI (Yamashita et al 2007). These findings raise the possibility that the inactivation gate may involve elements of the selectivity filter, as has been proposed for Ca V and K V channels.…”
Section: Ca 21 -Dependent Inactivation (Cdi)mentioning
confidence: 99%
“…4 E and Table 1) of Orai1 Y80E suggest that in addition to abrogating CDI, this mutation also significantly alters the pore structure. The interaction of permeation and inactivation gating has been described before for the Orai1 E106D mutant channel, an outer pore mutant with markedly decreased Ca 2+ affinity together with decreased CDI (Yamashita et al, 2007). Thus, an altered structure of the outer pore near the selectivity filter in Y80E may permit greater Ca 2+ flux while simultaneously preventing a conformational change that underlies CDI.…”
Section: Conformational Gating As a Candidate Mechanism For CDImentioning
confidence: 71%